Effect of three different veneering techniques on the stress distribution and in vitro fatigue behavior of core-veneer all-ceramic fixed partial dentures - Alexandre Luiz Souto Borges; Anna Karina Figueiredo Costa; Amanda Maria de Oliveira Dal Piva; Alana Barbosa Alves Pinto; João Paulo Mendes Tribst (Tabriz University of Medical Sciences, 2021)
Background. The present study aimed to evaluate the influence of the veneering technique on the tensile stress distribution and survival of full-ceramic fixed dental prostheses (FDPs). Methods. A three-dimensional model of an FDP was modeled on a second premolar and a second molar with a pontic between them for finite element analysis (FEA). The groups were divided according to the veneering technique: conventional stratification, rapid layer, and CAD-on techniques. A mesh control test determined the number of elements and nodes. The materials' properties were attributed to each solid component with isotropic, homogeneous, and linear elastic behavior. For the in vitro fatigue test (n=30), the FDPs were cemented on dentin analog abutments and submitted to 2×106 mechanical cycles (100 N at 3 Hz). Results. Maximum principal stress showed that the connector between the pontic and the second molar concentrated higher stresses, regardless of the techniques: Rapid layer (6 MPa)> CAD-on (5.5 MPa)> conventional stratification (4 MPa). The conventional stratification technique concentrated high stresses at the interface between the framework and veneering ceramic (2 MPa), followed by the rapid layer (1.8 MPa) and CAD-on (1.5 MPa) techniques. The crowns fabricated using the rapid layer and CAD-on techniques exhibited a 100% survival rate, while the conventional stratification group had 0% survival. Conclusion. Even with similar stress distribution between the veneering techniques, the conventional stratification technique was more prone to failure under fatigue due to higher defects incorporated than CAD-on and rapid layer techniques.